"I Decided to Save Them": Factors That Shaped Participation in Rescue Efforts during Genocide in Rwanda. (2nd March 2018) - Fox, Nicole; Nyseth Brehm, Hollie
Abstract: Collective action scholars have long examined why people choose to participate in social movements. This article argues that this body of scholarship can be productively applied to understanding rescue efforts during genocide, which have typically been associated with altruism and other psychological explanations. We analyze the case of Rwanda, where people worked collectively to save Tutsi from the violence that swept across the country in 1994, and ask: What social factors shaped Rwandans' decisions and abilities to save persecuted individuals? To address this question, we draw upon 35 in-depth interviews and a survey of 273 individuals who participated in rescue efforts, which constitutes one of the largest samples of rescue efforts to date. Although much previous literature has emphasized the role of stable personality traits in influencing such high-risk decisions, conceptualizing rescue as dynamic collective action enables us to examine social and contextual factors. Specifically, we illustrate how biographical availability, socialization, and situational contexts may influence rescue efforts. These findings contribute to scholarship on high-risk, clandestine collective action by illuminating how a combination of factors, including biographical availability, socialization, and situational contexts, coalesce to make rescue possible. As such, these findings inform our understanding of collective action that resulted in thousands of individuals being spared from torture, sexualized violence, and death.